TGF-β1 Provides Neuroprotection via Inhibition of Microglial Activation in 3-Acetylpyridine-Induced Cerebellar Ataxia Model Rats - Bei-Bei Cao; Bei-Bei Cao; Xiao-Xian Zhang; Xiao-Xian Zhang; Chen-Yu Du; Chen-Yu Du; Zhan Liu; Zhan Liu; Yi-Hua Qiu; Yi-Hua Qiu; Yu-Ping Peng; Yu-Ping Peng (Frontiers in Neuroscience, 2020)
Cerebellar ataxias (CAs) consist of a heterogeneous group of neurodegenerative diseases hallmarked by motor deficits and deterioration of the cerebellum and its associated circuitries. Neuroinflammatory responses are present in CA brain, but how neuroinflammation may contribute to CA pathogenesis remain unresolved. Here, we investigate whether transforming growth factor (TGF)-β1, which possesses anti-inflammatory and neuroprotective properties, can ameliorate the microglia-mediated neuroinflammation and thereby alleviate neurodegeneration in CA. In the current study, we administered TGF-β1 via the intracerebroventricle (ICV) in CA model rats, by intraperitoneal injection of 3-acetylpyridine (3-AP), to reveal the neuroprotective role of TGF-β1. The TGF-β1 administration after 3-AP injection ameliorated motor impairments and reduced the calbindin-positive neuron loss and apoptosis in the brain stem and cerebellum. Meanwhile, 3-AP induced microglial activation and inflammatory responses in vivo, which were determined by morphological alteration and an increase in expression of CD11b, enhancement of percentage of CD40 + and CD86 + microglial cells, upregulation of pro-inflammatory mediators, tumor necrosis factor (TNF)-α and interleukin (IL)-1β, and a downregulation of neurotrophic factor, insulin-like growth factor (IGF)-1 in the brain stem and cerebellum. TGF-β1 treatment significantly prevented all the changes caused by 3-AP. In addition, in vitro experiments, TGF-β1 directly attenuated 3-AP-induced microglial activation and inflammatory responses in primary cultures. Purkinje cell exposure to supernatants of primary microglia that had been treated with TGF-β1 reduced neuronal loss and apoptosis induced by 3-AP-treated microglial supernatants. Furthermore, the protective effect was similar to those treated with TNF-α-neutralizing antibody. These findings suggest that TGF-β1 protects against neurodegeneration in 3-AP-induced CA rats via inhibiting microglial activation and at least partly TNF-α release.